Deutsche Zeitschrift für Wirtschafts- und Insolvenzrecht (De Gruyter, 1991)
In the context of corporate insolvency and consumer insolvency proceedings, the Deutsche Zeitschrift für Wirtschafts- und Insolvenzrecht (DZWIR) [German Journal of Commercial and Insolvency Law] publishes articles relevant to the practice of commercial and insolvency law.